All About Animals - Cindy Franklin; Trisha Revels; Debra Summerall; Deborah J. Glauer (EDIS)
Produced by the Department of Family, Youth and Community Sciences in cooperation with the Florida 4-H Youth Development Program, University of Florida Cooperative Extension, Institute of Food and Agricultural Sciences, June, 1997; Reviewed June 2002.